2006
DOI: 10.1352/0895-8017(2006)111[290:btocbi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Treatment of Challenging Behaviors in Individuals With Mild Mental Retardation: Meta-Analysis of Single-Subject Research

Abstract: A meta-analytic study on effectiveness of behavioral and psychotherapeutic treatments for challenging behaviors in individuals with mild mental retardation is reported. Eighty articles were examined. For each comparison, several study variables and two effect sizes (percentage of nonoverlapping data-PND and percentage of zero data-PZD) were evaluated (Ms = 75% and 35%, respectively). Studies in which experimental designs and methods of experimental functional analysis were used had significantly larger PNDs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 22 publications
(37 reference statements)
9
93
1
Order By: Relevance
“…This conclusion corresponds to the findings of other meta-analyses published in this domain: Behavioral treatments are on average effective in reducing problem behavior in individuals with autism (e.g., Didden et al, 2006;Harvey et al, 2009;Heyvaert, Maes, & Onghena, 2010;Heyvaert, Maes, Van den Noortgate, Kuppens, & Onghena, 2012;Heyvaert, Saenen, Maes, & Onghena, 2014;Scotti et al, 1991;Vanderkerken, Heyvaert, Maes, & Onghena, 2013). However, for PZD the mean averages at the participant and study level indicated questionable treatment effects.…”
Section: Discussionsupporting
confidence: 88%
“…This conclusion corresponds to the findings of other meta-analyses published in this domain: Behavioral treatments are on average effective in reducing problem behavior in individuals with autism (e.g., Didden et al, 2006;Harvey et al, 2009;Heyvaert, Maes, & Onghena, 2010;Heyvaert, Maes, Van den Noortgate, Kuppens, & Onghena, 2012;Heyvaert, Saenen, Maes, & Onghena, 2014;Scotti et al, 1991;Vanderkerken, Heyvaert, Maes, & Onghena, 2013). However, for PZD the mean averages at the participant and study level indicated questionable treatment effects.…”
Section: Discussionsupporting
confidence: 88%
“…The variable Functional analysis/assessment provides an indication of the degree of quality of the behavioral intervention: Planning and conducting a solid functional analysis or assessment provides information on the function or the meaning of the challenging behavior, which can be taken into account when developing and conducting the intervention. This finding corresponds to the findings of the SCED meta-analyses of Campbell (2003), Didden et al (2006), and Harvey et al (2009).…”
Section: Merits and Drawbacks Of The Pnd And The Hlm Approach For Synsupporting
confidence: 89%
“…According to the Wald test included in the HLM approach, this reduction in challenging behavior was statistically significant. These PND and HLM findings correspond to the findings of other meta-analyses published in the domain of persons with disabilities: Behavioral interventions are on average effective in reducing challenging behavior in individuals with disabilities (Didden, Korzilius, van Oorsouw, & Sturmey, 2006;Harvey, Boer, Meyer, & Evans, 2009;Heyvaert, Maes, & Onghena, 2010;Heyvaert, Maes, Van den Noortgate, Kuppens, & Onghena, 2012;Heyvaert, Saenen, Maes, & Onghena, 2014b;Vanderkerken et al, 2013). Nonetheless, based on the likelihood ratio test included in the HLM approach, we found that the intervention effects varied significantly over the participants and studies included in the dataset.…”
Section: Merits and Drawbacks Of The Pnd And The Hlm Approach For Synsupporting
confidence: 87%
“…Several meta-analyses have identified ABA as an evidence-based practice to treat maladaptive behaviour and psychiatric disorders 24,25 in people with mild disabilities. 26 Meta-analyses have also established ABA as an effective or promising treatment for problem behaviour, such as SIB, [27][28][29] pica, 30 fear, and phobic avoidance. 31 Jennett and Hagopian 31 conducted a systematic review of treatments of phobic avoidance in people with IDs.…”
Section: Applied Behaviour Analysismentioning
confidence: 99%